2020
DOI: 10.1038/s41396-020-0685-4
|View full text |Cite
|
Sign up to set email alerts
|

Cheaters shape the evolution of phenotypic heterogeneity in Bacillus subtilis biofilms

Abstract: Biofilms are closely packed cells held and shielded by extracellular matrix composed of structural proteins and exopolysaccharides (EPS). As matrix components are costly to produce and shared within the population, EPS-deficient cells can act as cheaters by gaining benefits from the cooperative nature of EPS producers. Remarkably, genetically programmed EPS producers can also exhibit phenotypic heterogeneity at single-cell level. Previous studies have shown that spatial structure of biofilms limits the spread … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Here, we showed that in the initial stage of biofilm formation, the majority of the population was in an ON state, followed by heterogeneity in older biofilms. We show that in the timeframe between [16][17][18][19][20] hours, where an increase of robust pellicle biomass is the most pronounced (Fig 1D), there is a significant shift eps-expression intensity and switching ON of tasA expression in nearly all biofilm cells. Therefore, our results link temporal dynamics in matrix genes expression with temporal changes of robust biofilm biomass.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Here, we showed that in the initial stage of biofilm formation, the majority of the population was in an ON state, followed by heterogeneity in older biofilms. We show that in the timeframe between [16][17][18][19][20] hours, where an increase of robust pellicle biomass is the most pronounced (Fig 1D), there is a significant shift eps-expression intensity and switching ON of tasA expression in nearly all biofilm cells. Therefore, our results link temporal dynamics in matrix genes expression with temporal changes of robust biofilm biomass.…”
Section: Discussionmentioning
confidence: 80%
“…We began from a simple question: does phenotypic heterogeneity of matrix gene expression in B. subtilis (16,19,37) translate into non-uniform robustness within the biofilm? We will refer to such non-uniform biofilm robustness as "structural heterogeneity".…”
Section: Structural Heterogeneity Develops In Late Stages Of Pelliclementioning
confidence: 99%
“…Structural heterogeneity develops in late stages of pellicle growth. We began from a simple question: does phenotypic heterogeneity of matrix gene expression in B. subtilis (16,19,37) translate into nonuniform robustness within the biofilm? We will refer to such nonuniform biofilm robustness as "structural heterogeneity."…”
Section: Resultsmentioning
confidence: 99%
“…We began from a simple question: does phenotypic heterogeneity of matrix gene expression in B. subtilis ( 16 , 19 , 37 ) translate into nonuniform robustness within the biofilm? We will refer to such nonuniform biofilm robustness as “structural heterogeneity.” Biofilms were mechanically disrupted by vortexing with sterile glass sand ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation